2012
DOI: 10.4049/jimmunol.188.supp.46.30
|View full text |Cite
|
Sign up to set email alerts
|

Systemic 4-1BB activation induces a novel T-cell phenotype driven by high expression of Eomesodermin (46.30)

Abstract: Following treatment with 4-1BB agonist antibody, a novel population of KLRG1+ T-cells infiltrate murine melanoma. Compared to their KLRG1- counterparts, these T-cells express high levels of cytotoxicity associated genes in both the CD4 and CD8 lineages, and exhibit enhanced tumor-specific killing in vitro. The phenotype of these KLRG1+ cells is dependent on high expression of the T-box transcription factor Eomesodermin (Eomes). Interestingly, only activation of 4-1BB, not other TNFR family members generates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…These divergent results could potentially be due to over-activation resulting in AICD, induced upon Urelumab -41BB ligation. There have been reports regarding 41BB agonist-induced cytotoxicity and the strong activation and high induction of IL-2 production could potentially induce AICD in T cells exposed to Urelumab (65)(66)(67)(68). However, we did not observe evidence of enhanced cell death or reduced T cell numbers in stimulation cultures when Urelumab was present.…”
Section: Discussioncontrasting
confidence: 74%
“…These divergent results could potentially be due to over-activation resulting in AICD, induced upon Urelumab -41BB ligation. There have been reports regarding 41BB agonist-induced cytotoxicity and the strong activation and high induction of IL-2 production could potentially induce AICD in T cells exposed to Urelumab (65)(66)(67)(68). However, we did not observe evidence of enhanced cell death or reduced T cell numbers in stimulation cultures when Urelumab was present.…”
Section: Discussioncontrasting
confidence: 74%
“…Although Eomes expression was shown to limit Foxp3 induction, and thereby the suppressive function of Tregs (40), our data show that chronic CD27 engagement in CD11c-Cd70tg;CD27 +/mice did not alter the expression of Foxp3 (Figure 1B) nor their suppressive capacity, whereas transient engagement enhanced its expression (Figures 2B, 5A and Supplemental Figure 4A). The function of Eomes + TIGIT + Tregs remains to be determined but could be related to an increased cytotoxic mechanisms of suppression in vivo, as Eomes expression has been associated with enhanced cytotoxicity (41). Data in the literature show that Tregs, although dedicated to the inhibition of inflammatory responses, may produce IFN-g.…”
Section: Indicated That Elimination Of T-bet Expressing Tregsmentioning
confidence: 99%
“…This transcription factor, a paralogue of T-bet, appears to complement T-bet in triggering IFN-g in T lymphocytes (46) and was involved in the differentiation of cytotoxic CD4 + T cells. Curran et al (41) have shown that the activation of TNFR family receptors, in particular 4-1BB and to a lesser extent CD27, upregulated Eomes on CD4 + T lymphocytes. Eomes + KLRG1 + CD4 T cells displayed cytotoxic properties and expressed Granzyme B.…”
Section: Effect Of Cd27 Engagement On Tconvsmentioning
confidence: 99%
“…This transcriptional reprogramming resembles that of CD8 + versus CD4 + lineage commitment during T cell development and induces expression of more genes classically involved in cytotoxic CD8 + T cell differentiation, including CD8a, T-bet, Eomes, and GzmB (13)(14)(15)(16). Other factors that have been shown to stimulate CD4 + CTL differentiation include signaling via 4-1BB, OX40, and IL-2 receptors (17)(18)(19)(20)(21). In contrast, the T follicular helper (Tfh) differentiation program antagonizes CD4 + CTL differentiation (via upregulation of the transcription factor Bcl6), as does signalling mediated by the inhibitory receptors PD-1 and LAG3 (16).…”
Section: Introductionmentioning
confidence: 99%